Analisis Uji Beda Rata-Rata Curah Hujan Tahunan Di Stasiun Aseman Dan Sumerta Pada Das Tukad Mati - Desfinta, Tiara Dwi (Tech : Journal of Engineering Science, 2026)
This study aims to analyze and compare the average annual rainfall at Aseman Station and Sumerta station, which are located within the Tukad Mati River Basin (DAS). This comparisob is crucial to determine the extent to which data from both stations can be used comparatively and consistently in regional hydrological planning, such as evaluating water availability or calculating flood discharge. The method used in this study is quantitative descriptive, with annual rainfall data for the late 10 years (2014-2023). Statistical analysis was performed using SPSS (Statistical Package for the Social Sciences) software. The initial step of the analysis was the Shapiro-Wilk Normality Test, which showed that the average annual rainfall data at both stasion was normally distributed (Aseman Station Sig.=0.220; Sumertas station Sig.=0.578). Since the normality assumption was met, the analysis continued using a parametric statistical test, namely the Paired Sampel T-Test. Statistically, the average rainfall at the Aseman station is 1.77530 mm, while at the Sumerta station it is 1.5674 mm. The results of the Paired Samples T-Test show a Significance value (Sig.2-tailed) of 0.005. Because the value 0.005 is smaller than 0.05. This study proves that there is a statisticaly significant difference in the average annual rainfall between the Aseman station and the Sumerta station in the Tukad Mati watershed.